2016
DOI: 10.1111/psyp.12812
|View full text |Cite
|
Sign up to set email alerts
|

Early and late brain signatures of emotional prosody among individuals with high versus low power

Abstract: Psychophysiology 2Using event9related brain potentials (ERPs), we explored the relationship between social power and emotional prosody processing. In particular, we investigated differences at early and late processing stages between individuals primed with high or low power. Comparable to previously published findings from non9primed participants, individuals primed with low power displayed differentially modulated P2 amplitudes in response to different emotional prosodies, whereas participants primed with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, Power × Pain interaction absent in the P2 and P3 components, indicating that the social power of participants might not modulate empathic responses to others’ pain. The interaction of Power × Pain was statistically non-significant, which was not consistent with the result of Paulmann and Uskul (2017). In their study, the same power priming procedure was used to induce the sense of high or low power, and, then participants were asked to judge six different emotional voice.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, Power × Pain interaction absent in the P2 and P3 components, indicating that the social power of participants might not modulate empathic responses to others’ pain. The interaction of Power × Pain was statistically non-significant, which was not consistent with the result of Paulmann and Uskul (2017). In their study, the same power priming procedure was used to induce the sense of high or low power, and, then participants were asked to judge six different emotional voice.…”
Section: Discussionmentioning
confidence: 78%
“…For Paulman & Uskul’s Emotion x Power interaction effect on P2, ηp2 = 0.08, 90%CI for ηp2 = 0.02, 0.12, omega 2 p = 0.06. However, as our research design was different from that of Paulmann and Uskul (2017), it is impossible to compare your partial eta 2 with theirs. Yet, the results mentioned above would help researchers to get better understanding of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, a basic sensory encoding of physical properties (e.g., pitch and loudness) occurs around 100 ms after stimulus onset with a negative peak. N100 modulation by emotionality is controversial and rarely observed for emotional speech processing (Pell et al, 2015;Paulmann and Uskul, 2017) for no modulation observed, and (Pinheiro et al, 2015) for higher negativity for happiness vs. anger. Sensorial analyses are followed by salience appraisal in which emotional cues are integrated.…”
Section: Introductionmentioning
confidence: 99%